Efek Penambahan Garam Pada Tanah Gambut Untuk Daya Dukung Tanah - Indra Saputra; Muhammad Ridha (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Adding salt to the original soil can reduce the optimum moisture content and increase the maximum dry volume weight at a percentage of 0% by 0.8913 gr / cm3 - 10% by 1.0593 gr / cm3. CBR testing that is not submerged in the original soil will improve the mechanical properties of the soil if mixed with 5% of 8.37 kg / cm2, then a decrease of 10% is 3,297 kg / cm2 and so on because it is easy to dissolve and has low bond strength. So, the CBR shows that its value decreases dramatically as the percentage salt increases. Testing the value of the shear angle (Ø) also continues to fall with increasing value of the percentage of Salt. In cohesion testing also increased at 5% by 0.089 kg / m2 and decreased if the percentage of salt addition increased. The value of shear strength also increased at a percentage of 0% by 26.57o - 10% by 39.29 and decreased at a higher percentage. The addition of salt to native soil can also increase the shear strength value of 5% salt by 0.209 - 10% salt by 0.351 kg / cm2 and decrease at 15% higher salt addition by 0.140kg / cm2.